COVID-19 Vaccine Hesitancy among French People Living with HIV - Alexandre Vallée; Erwan Fourn; Catherine Majerholc; Pauline Touche; David Zucman (Vaccines, 2021)
People living with HIV are a high-risk population concerning the coronavirus 19 (COVID-19) infection, with a poorer prognosis. It is important to achieve high COVID-19 vaccination coverage rates in this group as soon as possible. This project used self-reporting to assess vaccine hesitancy and acceptance among people living with HIV towards the novel COVID-19 vaccine. Sixty-eight (28.7%) participants among the 237 declared their hesitancy to be vaccinated against COVID-19. Participants who expressed concerns about their health (p < 0.001), the requirement of mandatory COVID-19 vaccination (p = 0.017), and their chronic disease status (p = 0.026) were independently associated with the acceptance of vaccination. Conversely, participants presenting general vaccine refusal (p < 0.001), concerns about the serious side effects of COVID-19 vaccines (p < 0.001), and those already thinking having an immune status to COVID-19 (p = 0.008) were independently associated with COVID-19 vaccine hesitancy. Our results suggest that vaccine strategy would be more successful in France with a communication strategy emphasizing the collective benefits of herd immunity in the population living with HIV and reassuring patients with chronic diseases about the safety of the proposed vaccines.